2007
DOI: 10.1089/scd.2007.9993
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of a Novel Human Cord Blood-Derived Neural-Like Stem Cell Line in a Rat Model of Cortical Infarct

Abstract: Umbilical cord blood can be a rich source of stem/progenitor cells, not only for hematopoetic but also for other tissue-specific lineages. Recently, we have developed a novel, self-renewed neural-like stem cell line named HUCB-NSC from human cord blood. To test if HUCB-NSCs can supply brain in need of regeneration, we injected these cells into immunosuppressed intact rat forebrain and to animals suffering from a photothrombotic cortical lesion at 48 h after injury. The survival, migration, and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Seven days after transplantation high number of these cells exhibited neuronal phenotypes (NF-200) and, to lower extend, glial (GFAP, S-100β) cell markers. Some of these cells survived for 4 weeks; however most of them disappeared during this time, despite of employed CsA immunosuppression (Kozlowska et al, 2007). These results agree with other reports where only a few transplanted HUCB cells were found in injured CNS at 4-6 weeks after transplantation (Liu et al, 2006;Kuh et al, 2005).…”
Section: The Cord Blood Challenge For Brain Repairsupporting
confidence: 90%
“…Seven days after transplantation high number of these cells exhibited neuronal phenotypes (NF-200) and, to lower extend, glial (GFAP, S-100β) cell markers. Some of these cells survived for 4 weeks; however most of them disappeared during this time, despite of employed CsA immunosuppression (Kozlowska et al, 2007). These results agree with other reports where only a few transplanted HUCB cells were found in injured CNS at 4-6 weeks after transplantation (Liu et al, 2006;Kuh et al, 2005).…”
Section: The Cord Blood Challenge For Brain Repairsupporting
confidence: 90%
“…In vitro by RT-PCR, alizarin red and von Kossa-staining, ALP detection, immunohistochemistry and western blot 8,31,[110][111][112][113] In vitro by safranin-O staining, RT-PCR and immunohistochemistry 8,31 In vitro by immunohistochemistry, RT-PCR, calcium imaging and western blot [114][115][116][117] In vivo in parkinsonian rat model, ischemic rat model [118][119][120][121][122][123] In vitro by immunohistochemistry, RT-PCR, PAS-staining, urea and albumin production, western blot and LDL uptake 31,94,124,125 CD34/AC133-positive (hematopoietic progenitor) cells In vitro by RT-PCR 126 In vivo in NOD/SCID mouse model 95,96 Not defined cells from MNC In vitro by immunohistochemistry, whole-cell patch-clamp, western blot and RT-PCR [127][128][129][130][131] In vivo in spinal cord injury and intra-brain injection in rat and NOD/SCID mouse model 73,76,[80][81][82][83][84][86][87][88][89][90][91][92]<...>…”
Section: Mscmentioning
confidence: 99%
“…In subsequent studies, few UCB cells have been found to survive in the brain of stroked rats or mice. Even in studies that have used UCB derived cells that have undergone neural induction prior to transplantation into infarcted cortex, there was a paucity of cells (Kozłowska et al 2007). …”
Section: Cell Replacementmentioning
confidence: 99%